Reclaiming English language arts methods courses : critical issues and challenges for teacher educators in top-down times - Brass, Jory; Webb, Allen, 1957- (New York : Routledge, 2015)
Reclaiming English Language Arts Methods Courses showcases innovative work in teacher education that fosters teachers' capacities as reflective practitioners and public intellectuals; extends traditional boundaries of methods courses on teaching the English language arts, literacy, and children's and young adult literature; and embodies democratic and critical politics that go beyond the reductive economic aims and traditional classroom practices sanctioned by educational policies and corporate educational reforms. Featuring leading and emerging scholars in English language arts teacher education, each chapter provides rich and concrete examples of elementary and secondary methods courses rooted in contemporary research and theory, online resources, and honest appraisals of the possibilities, tensions, and limits of doing teacher education differently in a top-down time of standards-based education, high-stakes testing, teacher assessment, and neoliberal education reforms. This book offers important resources and support for teacher educators and graduate students to explore alternative visions for aligning university methods courses with current trends in English and cultural studies, critical sociocultural literacy, new literacies and Web 2.0 tools, and teaching the English language arts in multiethnic, multilingual, and underserved urban communities. The Companion website to this book [www.ReclaimingEnglish.com] makes available contributing authors' course syllabi, signature readings, course projects, and assessment tools to provide teacher educators with resources to support innovation and change in other teacher education programs. Book jacket.
Includes bibliographical references and index.
Keywords: Language arts; English language -- Study and teaching; English teachers -- Training of; English teachers -- In-service training